It's Not Education by Zip Code Anymore - But What is It? Conceptions of Equity under the Common Core - Mindy Laura Kornhaber; Kelly Griffith; Alison Tyler (Arizona State University, 2014)
The Common Core State Standards Initiative is a standards-based reform in which 45 U.S. states and the District of Columbia have agreed to participate. The reform seeks to anchor primary and secondary education across these states in one set of demanding, internationally-benchmarked standards. Thereby, all students will be prepared for further learning and work in a competitive global economy regardless of the sociodemographic variation associated with their "zip code," that is, the location of their neighborhood or school. This article examines the role and meaning of equity within the Common Core at a level beyond "zip code." It does so using data from interviews with Common Core policy entrepreneurs and qualitative analysis of interview data. Findings are considered against a conceptual framework of equal, equalizing, and expansive views of equity. The findings indicate that policy entrepreneurs hold primarily an equal view of equity, in accord with meritocratic and functional purposes of schooling, more so than equalizing or expansive views. The latter views emphasize compensatory purposes that focus on narrowing achievement gaps. From this analysis, we identify the paradox of equity in education policy: The successful launch of a policy that relies on existing paradigms of standards-based reform and an equal conception of equity helps tether educational outcomes to student background.